The innovation and practice of the “hand as foot” teaching method in the teaching of Parkinson’s disease - Yang, Jingjing; Yang, Dandan; Yu, Jie; Liu, Jiahui (Frontiers in Aging Neuroscience, 2025)
BackgroundBased on years of clinical teaching experience, the orthopedic team pioneered the “hand as foot” teaching method, initially applied in orthopedic teaching. The advantage of “hand as foot” teaching lies in the high similarity of anatomical structures between upper and lower limbs, joints, nerves, blood vessels, etc., This method allows using feet to explain knowledge instead of hands. It has since expanded to internal medicine, surgery, obstetrics, and gynecology, significantly impacting clinical teaching and medical education across departments. Utilizing simple gestures or body language to grasp clinical knowledge intuitively and repeatedly has proven effective. Over years of theoretical teaching, understanding brain anatomy, particularly the anatomy and communication of Parkinson’s disease (PD), has posed challenges. Recently, after consulting relevant literature and articles on the application of the “hand as foot” teaching method in clinical teaching, I have been inspired. The invisibility and inaccessibility of brain anatomy make it challenging for students to comprehend and retain knowledge of basal ganglia anatomy. Through numerous clinical teaching experiences, we have discovered that using “hand as foot” is well-suited to address these teaching difficulties. Although there are many existing articles on manualized teaching methods in various disciplines, there is a gap in research on the impact of “hand as foot” method on students’ academic performance. The aim of this study was to investigate the impact of the “hand as foot” teaching method on knowledge related to PD.MethodsA self-designed questionnaire was used to validate the effectiveness of the “Hand and Foot” teaching method for teaching key points to undergraduate clinical medical students in Inner Mongolia Medical University.ResultsThere were a total of 81 participants of which 41 were in class 1 (students using “hand as foot” teaching method) and 40 were in class 2 (students using “hand as foot” teaching method), 75.61% of the students in class 1 found the “hand as foot” method useful and only 19.51% found the “hand as foot” method average. Of the students who were taught “hand as foot,” 80.49% correctly answered the option “Main pathological changes in PD.” A total of 70.73% correctly answered the option “Main components of the basal ganglia.” A total of 82.93% correctly answered the option “Typical symptoms of PD.” A total of 51.22% correctly answered the question related to the swallow tail sign. The percentage of correct answers was much higher than that of the students in the class 2. From the questionnaire survey of medical students’ knowledge of PD, we can draw several important conclusions. A total of 75.61% of the students in class 1 who had used the “hand as foot” method teaching in PD found the method helpful. The results with statistical difference (P < 0.05) showed that the “hand as foot” teaching method directly affected the students’ knowledge about PD.ConclusionThe “hand as foot” teaching method is generally well-received by medical students. The teacher-student interaction is good, and the understanding and memorization of difficult knowledge points are effective. It also helps visualize knowledge and strengthens students’ understanding and memory of complex concepts. This teaching approach has garnered positive feedback from both teachers and students. As basic education evolves, classroom teaching methods are continuously being reformed and advanced. Therefore, it is crucial to establish engaging teaching methods in the classroom. The analogy teaching method effectively stimulates students’ interest in learning and encourages their self-directed learning. In comparison to the indoctrination teaching model, which focuses on rote memorization, this teaching method is more likely to spark students’ interest in knowledge and boost their enthusiasm for learning. The results showed that the “hand as foot” teaching method significantly improved the correctness of the knowledge related to PD. In general, the use of “hand as foot” in the classroom can enliven the educational environment and enhance students’ understanding and retention of abstract concepts. It aids in consolidation and review after class, simplifying complex questions into an intuitive and concrete form, which is highly beneficial for clinical teaching.